Ambient intelligence for health : first International Conference, AmIHEALTH 2015, Puerto Varas, Chile, December 1-4, 2015, proceedings /: first International Conference, AmIHEALTH 2015, Puerto Varas, Chile, December 1-4, 2015, proceedings. (2015) - Unknown
No abstract available